The Influence of Environmental Knowledge, Perceived Green Value, and Perceived Behavioral Control on Green Consumer Behavior of Organic Food Products - Seniorita; Niken Savitri Primasari; Apriani Riyanti; Rina Feriana; Sumarni; M. Rasda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The primary aim of this study is to analyze the impact of various treatments such as environmental awareness, perceived green value, and perceived behavioral control on the consumers of organic food. The research takes into consideration the scenario where consumers are increasingly accepting eco-friendly products due to their awareness of the environment and their demand for food products which are less harmful or safe for nature. To achieve this, the researchers used a quantitative explanatory approach involving 150 participants with prior experience of organic food products. While purposive sampling was employed to assure knowledgeable and experienced respondents with respect to the organic products. The questionnaire was subjected to item-total validity testing, Cronbach's Alpha reliability testing, and classical assumption testing before the application of multiple linear regression analysis. The findings showed that the three independent variables had a positive and significant effect on green consumption behavior. The determined values of the coefficient of determination indicated that environmental knowledge, perceived green value, and perceived behavioral control together characterized consumer behavior. This study, on the one hand, contributes theoretically by adding to the knowledge of the green consumer behavior and the psychological factors that influence it. On the other hand, the findings of the study offer ways for the industry players to improve their educational strategies by enhancing the green value of their products and making organic products more available as a manner of promoting sustainable consumption behavior.